Understanding tuberculosis among people with tuberculosis through an educational film: a qualitative study - Olivia Biermann; Johanna Kuhlin; Lina Davies Forsman; Kristi Sidney Annerstedt; Asli Kulane; Elin Economou Lundeberg (BMJ Open)
Introduction Treatment of the two billion people with tuberculosis (TB) infection worldwide is crucial to prevent progression to TB disease and thereby prevent further transmission. However, TB is associated with fear and stigma, and knowledge gaps about TB disease are widespread, complicating adherence to treatment. As increasing knowledge about TB can reduce stigma and increase adherence to treatment, we developed an educational film about TB infection and disease. After showing the film to people with TB, our qualitative study aimed to evaluate the film and to explore perceptions, fears and possible knowledge gaps.Method We conducted a qualitative study, with in-depth interviews (n=13), at two Infectious Disease Outpatient Departments in Sweden. Included research participants were adults with TB infection or TB disease. After informed consent, the participants watched the film, available in Swedish, English, Somali and Tigrinya. Subsequently, in-depth interviews, using a topic guide, were conducted, transcribed, and a reflexive thematic analysis was performed.Results All participants considered the film to be a valuable addition to the written and oral information they had previously received. Identified themes included the perception of TB infection being a deadly, non-curable disease, and many feared being contagious. However, the film challenged these fears and increased the understanding of TB infection being treatable and non-infectious. Another theme revealed that TB-related stigma was experienced in encounters with healthcare professionals in Sweden.Conclusion Our educational film was perceived to increase understanding about TB symptoms, transmission and treatment. Implementing the film in Infectious Disease Departments across Sweden may contribute to decreasing stigma and enhancing awareness of the importance of treatment adherence, an outcome that warrants further investigation post-implementation.